Adsorpsi Ion Pb(II) Menggunakan Silika Berbasis Pasir Alam Takari-NTT : Ion Pb(II) Adsorption Using Silica from Natural Sand of Takari-NTT - Johnson N. Naat (KOVALEN: Jurnal Riset Kimia, 2022)
This article reported the adsorption of Pb(II) ions using silica extracted from the natural sand of Takari, Timor island, Nusa Tenggara Timur province. The silica was extracted using hydrothermal and coprecipitation methods. The extracted silica was then used for Pb(II) adsorption under several optimization conditions: pH, contact time, concentration, kinetic model, and adsorption isotherm. The determination of Pb(II) concentration used dithizone reagent, forming complexes, and then measured using Uv-Vis. The pH, contact time, and optimum concentration results were 7, 60 minutes, and 80 mg/L, respectively, with an adsorption capacity (qe) of 0.679 mg/g, 0.745 mg/g, and 18.096 mg/g. The kinetic model followed a pseudo-order-2 with R2 = 0.93, and the adsorption isotherm of Pb(II) metal ions followed the Temkin isotherm model. The results showed that the silica extracted from the natural sand of Takari of Timor island-Nusa Tenggara Timur could adsorb Pb(II) metal ions